Training, leadership style, and work environment on employee performance: The role of work motivation - Putri, Dheya Kusuma Arianing; Hartono, Arif (Universitas Ahmad Dahlan, 2023)
Organizations must have a strategy to improve employee performance. One of the strategies is to provide training, evaluate the leadership style applied by the head of the field, and create a comfortable work environment, which can be a solution to improve employee performance. This research is a quantitative data collection tool questionnaire with a sample of 99 employees using the partial least square analysis tool. The results of this study indicate that leadership style training and the work environment have a positive effect on work motivation. Training, leadership style, work environment, and motivation have a positive effect on employee performance. Work motivation mediates the relationship between training and employee performance. Work motivation mediates the relationship between leadership style and employee performance. Work motivation mediates the relationship between the work environment and employee performance.